2012
DOI: 10.1634/theoncologist.2012-0173
|View full text |Cite
|
Sign up to set email alerts
|

Patient–Clinician Information Engagement Improves Adherence to Colorectal Cancer Surveillance after Curative Treatment: Results from a Longitudinal Study

Abstract: Introduction. Follow-up surveillance after curative treatment for colorectal cancer (CRC) patients is recommended to detect early cancer recurrences and improve survival outcomes. However, a substantial proportion of CRC patients do not undergo cancer surveillance. Several demographic and disease-related factors have been associated with cancer surveillance adherence. Thus far, patientcentered communication has not been studied as a determinant for undergoing cancer surveillance. The purpose of this study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…A study of nonmetastatic CRC survivors showed that 31% of survivors did not believe they were at risk for recurrence or secondary cancers, which could suggest either lack of knowledge of risks, or optimism [23]. In addition, higher patient-physician engagement, as measured by the PatientClinician Information Engagement Scale (PCIE), was Cancer Causes Control associated with self-reported CRC adherence in a longitudinal study [24]. Other previous studies also indicate that patient-centered communication with providers increases the quality of these relationships and adherence with regimens [25].…”
Section: Discussionmentioning
confidence: 99%
“…A study of nonmetastatic CRC survivors showed that 31% of survivors did not believe they were at risk for recurrence or secondary cancers, which could suggest either lack of knowledge of risks, or optimism [23]. In addition, higher patient-physician engagement, as measured by the PatientClinician Information Engagement Scale (PCIE), was Cancer Causes Control associated with self-reported CRC adherence in a longitudinal study [24]. Other previous studies also indicate that patient-centered communication with providers increases the quality of these relationships and adherence with regimens [25].…”
Section: Discussionmentioning
confidence: 99%
“…This concept has been demonstrated in other gastrointestinal diseases requiring surveillance or ongoing follow-up. For example, increased adherence to surveillance protocols after colorectal cancer treatment is higher in patients with higher baseline patient-clinician information engagement scores 18 ; and a study of an outpatient inflammatory bowel disease clinic shows that physician trust is correlated with increased overall adherence to therapy and increased adherence to medications. 19 Other social and demographic factors that we examined did not appear to be associated with treatment adherence, including age, gender, marital status, insurance payor and driving distance from the treatment center.…”
Section: Discussionmentioning
confidence: 99%
“…Increased patient-driven communication about cancer-related health information could in turn improve a variety of health outcomes [42]. For instance, cancer patients who are information seekers are more likely to adopt healthy lifestyles, be adherent to surveillance, and have improved psychosocial outcomes than non-seekers [11, 29, 43, 44]. The absolute size of the detected effect of DTCA exposure on information seeking behavior is small, but if this effect is relevant to a large number of patient-clinician interactions, the population effect on health outcomes could be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…This measure is adapted from prior studies and comprised 6 binary items (yes/no) [29]. Participants were asked to recall if they 1) actively looked for information about their cancer (about treatments but also about other topics) from their doctors, 2) actively looked for information about their cancer from other doctors or health professionals, 3) actively looked for information about quality of life issues from their doctors, 4) actively looked for information about quality of life issues from other doctors or health professionals, 5) discussed information from other sources with their doctors, and 6) received suggestions from their doctors to go to other sources for more information.…”
Section: Methodsmentioning
confidence: 99%